C++ for impatient - Overland, Brian (Addison-Wesley, 2013)
C++ for the Impatient offers both the quickest way for busy programmers to learn the latest features of the C++ language and a handy resource for quickly finding answers to specific language questions. Designed to give you the most accurate and up-to-date information you require fast and to the point, this book is also an essential guide to the new C++11 standard, including advanced uses of the C++ standard library.